Prevalensi Kelainan Kulit pada Masa Kehamilan - Rizkia Chairani Asri; Suri Emilia Annisa (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Hormonal, vascular, immunological and metabolic changes in pregnancy can cause many changes in body systems. This condition has an impact on skin changes associated specifically with pregnancy (dermatoses in pregnancy).  These changes can be physiological or pathological.  This condition is usually considered normal and ignored by health workers but can affect the quality of life in pregnant women. This study was conducted to determine the prevalence of both physiological and pathological skin changes in pregnancy.  In this systematic review, literature was reviewed through three databases in accordance with the 2020 PRISMA guidelines. Inclusion criteria were primary literature or journals, full text, in English or Indonesian, published in 2013-2023, examined the prevalence of skin disorders in pregnancy, cross-sectional study design sectionals, cohorts.  The study that cannot be accessed in full text and in the form of a review is excluded from the literature review.  Most skin disorder changes in pregnant women are in the form of physiological disorders with the type of hyperpigmentation.  While the most pathological changes are Atopic Eruption of Pregnancy (AEP) and Polymorphic Eruption of Pregnancy (PEP).